2022
DOI: 10.1002/advs.202203162
|View full text |Cite
|
Sign up to set email alerts
|

Assembly: A Key Enabler for the Construction of Superior Silicon‐Based Anodes

Abstract: Silicon (Si) is regarded as the most promising anode material for high-energy lithium-ion batteries (LIBs) due to its high theoretical capacity, and low working potential. However, the large volume variation during the continuous lithiation/delithiation processes easily leads to structural damage and serious side reactions. To overcome the resultant rapid specific capacity decay, the nanocrystallization and compound strategies are proposed to construct hierarchically assembled structures with different morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 181 publications
0
31
0
Order By: Relevance
“…To meet the rising demand of electric vehicles for high-energy-density lithium-ion batteries (LIBs), Si-based materials show great promise as high-capacity anodes as a result of high theoretical capacity (3579 mAh g –1 for Li 15 Si 4 ), environmental friendliness, and low cost. Nevertheless, the commercial application of a Si-based anode is still limited by its high volume variation and low electronic conductivity (10 –5 –10 –3 S cm –1 ) and ion diffusion coefficient (10 –14 –10 –13 cm 2 s –1 ), which are the main reasons for the poor cycle stability and fast charge performance. …”
Section: Introductionmentioning
confidence: 99%
“…To meet the rising demand of electric vehicles for high-energy-density lithium-ion batteries (LIBs), Si-based materials show great promise as high-capacity anodes as a result of high theoretical capacity (3579 mAh g –1 for Li 15 Si 4 ), environmental friendliness, and low cost. Nevertheless, the commercial application of a Si-based anode is still limited by its high volume variation and low electronic conductivity (10 –5 –10 –3 S cm –1 ) and ion diffusion coefficient (10 –14 –10 –13 cm 2 s –1 ), which are the main reasons for the poor cycle stability and fast charge performance. …”
Section: Introductionmentioning
confidence: 99%
“…With the booming demand of portable electronics, hybrid and electric vehicles and renewable energy storage systems, Li-ion batteries (LIBs) have become the most attractive electrochemical energy utilization devices due to their high energy and power density, suitable operating voltage, and low selfdischarge. [1][2][3][4][5] However, the limited theoretical specic capacity (372 mA h g −1 ) of graphite, which is commonly used as the anode material, struggles to meet the requirement for the high energy density of next-generation LIBs. [6][7][8][9][10] Endowed with exceptional specic capacity (4200 mA h g −1 ) and low reduction potential (<0.5 V), the silicon anode substance has been developing as a promising substitute for high energy density LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…18 When considering the superiorities of chemical stability, mechanical strength, excellent electrical/ionic conductivity and permanent skeleton, carbon-based materials have gained much favor in the engineering upgrade of tailoring structures. 2,3,7,[19][20][21] To conquer the above technical issues, integrating the naked silicon substance with a multitudinous carbonaceous matrix, such as commercial carbon nanotubes, graphene, manufactured carbon, or others, to construct felicitous silicon-carbon micro-skeletons (e.g., hierarchical pores and embedding/ doping engineering and core-shell structures) has been a feasible countermeasure. 1,11,[22][23][24][25] As a result, researchers have proposed a number of nanostructured silicon-carbon materials, including silicon/carbon nanotubes, silicon/porous-carbon composites and silicon/graphene, to improve the cycling stability of silicon anodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,24–29 In recent years, NP assemblies have come under the spotlight as high-performance anode materials for LIBs owing to their lower interfacial area compared to that of NPs, which can significantly reduce the interparticle resistance and mitigate the risk of side reactions. 25,26 In addition, their high tap density results in thinner electrodes at the same mass loading, which allows shorter electron pathways and increases the volumetric specific capacity of the whole cell. 25,26 Recently, it has been reported that the electrochemical performance of the NP-assembly electrodes can be improved by a robust interconnection of the NPs.…”
Section: Introductionmentioning
confidence: 99%